Peran Pengawas Sekolah Selaku Pelaku Supervisi Pendidikan dalam Meningkatkan Mutu Manajemen Pendidikan - Fatmariyanti, Yanti; Qurtubi, Qurtubi; Bachtiar, Machdum (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The implementation of educational and learning activities in an educational institution will be able to realize a program of improving the quality of education if there is a guidance to apply managerial and academic systems. Therefore, there is a need for the role of school supervisors as educational supervisors who play an important role in the success of the school. The aim of this research is to understand, reveal and explain in detail how educational supervisors play a role in advancing the quality of education management in educational institutions. The method used in this research is a qualitative method, by obtaining data and sources of information from reading literature such as books, written articles, statutory regulations (library research) obtained either via the internet or personal collections. After going through research and analysis, the results showed that supervisors, in this case school supervisors, in advancing the quality of education management in an educational institution play a significant role in providing guidance, assistance and guidance to school principals and teachers